BIOSYNTHESIS AND CHARACTERIZATION OF CuO NANOPARTICLES USING DIFFERENT pH - Omar, Sanya S.; Mohammed, Raghad Y. (Science Journal of University of Zakho, 2023)
CuO nanoparticles are synthesized from Ferulago angulate leaf extract under different pH values. The structural, morphological, as well as optical properties of the green synthesized CuO NPs are studied. Besides, the functional groups in the Ferulago angulate stabilizer capping the copper nanoparticles were examined using FTIR spectra. The primary factor that led to the first confirmation of CuO NP production was the reaction mixture’s color change. A phytochemical test revealed the presence of proteins, amino acids, carbohydrates, flavonoids, phenols, alkaloids, tannins, and saponins. FTIR spectrum shows a peak at 532.35 cm-1, this may be attributed to CuO’s vibrations confirming the presence of copper oxide nanoparticles. XRD analysis shows the presence of crystalline monoclinic cupric oxide (CuO). The morphological study (FESEM) shows different morphology (different shapes and sizes) under different pH values. EDS data shows the O-richness of the prepared CuO NPs extracted from Ferulago angulate [ Schltdl.] BOISS leaf extract shows pure CuO phases. In this investigation, fabricated CuO’s estimated energy band gap values were higher than those of bulk CuO. Results show Eg increment with increasing pH values.